Serum levels of iron, zinc, selenium, copper and oxidative stress in hypertensive patients: A comparative study of age-related changes in the governorate of Basrah, Iraq - Abid Al-Hussain Hameed, Maha; Ghareb Sayyah, Sahera (Edelweiss Applied Science and Technology, 2024)
Hypertension is the force of blood through blood vessels, where the heart works harder and blood vessels are under more pressure. The relationship between trace element levels and oxidative stress in hypertension is under investigation, with conflicting results. This study aimed to determine the relationship between concentrations of certain antioxidant trace elements (iron, zinc, selenium, and copper) and protein carbonyl concentration as an indicator of oxidative stress in the serum of hypertensive patients compared to the control group in Basra, Iraq, according to age. The study included 100 hypertensive patients (44 males and 56 females) compared to 50 healthy individuals (25 males and 25 females). Patients were divided into three age groups: 35–45, 46–56, and over 57 years. The study showed a significant decrease (p<0.001) in the mean concentration of all selected elements in the patients' serum compared to the control group. Conversely, the mean protein carbonyl level showed a significant increase (p<0.001) in patients compared to the control group. Trace element concentrations decreased in patients with increasing age, while carbonyl protein levels increased, especially in the third age group. The study also showed a significant negative correlation between protein carbonyl level and all trace elements at p<0.001. These results suggest that hypertension is associated with an imbalance in oxidative stress and trace elements. Monitoring trace element intake may help reduce oxidative stress and improve overall health in individuals with hypertension, especially with advancing age, by restoring the balance of essential elements and antioxidants in the body.